Instrumentation reference book - Boyes, Walt (Butterworth-Heinemann/Elsevier, 2010)
Instrumentation embraces the equipment and systems used to detect, track and store data related to physical, chemical, electrical, thermal and mechanical properties of materials, systems and operations. While traditionally a key area within mechanical and industrial engineering, it also has a strong presence in electrical, chemical, civil and environmental engineering, biomedical and aerospace engineering. The discipline of Instrumentation has grown appreciably in recent years because of advances in sensor technology and in the inter-connectivity of sensors, computers and control systems. In turn, this has meant that the automation of manufacturing, process industries, and even building and infrastructure construction has been improved dramatically. And now with remote wireless instrumentation, heretofore inaccessible or widely dispersed operations and procedures can be automatically monitored and controlled. The new 4th edition of this already well-established reference work, will reflect these dramatic changes with improved and expanded coverage of the both the traditional domains of instrumentation as well as the cutting edge areas of digital integration of complex sensor/control systems. Thoroughly revised, with up-to-date coverage of wireless sensors and systems, as well as nanotechnologies role in the evolution of sensor technology Latest information on new sensor equipment, new measurement standards, and new software for embedded control systems, networking and automated control Three entirely new sections on Controllers, Actuators and Final Control Elements; Manufacturing Execution Systems; and Automation Knowledge Base Up-dated and expanded references and critical standards.
Keywords: Physical instruments -- Handbooks, manuals, etc.; Engineering instruments -- Handbooks, manuals, etc.; elektronické knihy; electronic books